Controlled Synthesis of Sb2O3 Nanoparticles, Nanowires, and Nanoribbons. (23rd March 2006) - Ye, Changhui; Wang, Guangye; Kong, Mingguang; Zhang, Lide
Abstract : Sb 2 O 3 nanoparticles, nanowires, and nanoribbons have been selectively synthesized in a controlled manner under mild conditions by using CTAB as a soft template. By adoptingSb ( OH ) 4 − as an inorganic precursor and the concentration of CTAB as an adjusting parameter, morphologies ofSb 2 O 3 nanostructures can be selectively controlled. Typically, C CTAB < 0.15 mmol favors the formation of nanoparticles (product one or short form P1); when the concentration of CATB is in the range 0.15–2.0 mmol, nanowires (P2) dominate the products; nanoribbons (P3) form above the concentration of 2.0 mmol, and when the concentration of CTAB goes further higher, treelike bundles of nanoribbons could be achieved. The method in the present study has potential advantages of easy handling, relatively low-cost, and large-scale production. The facile and large-scale synthesis of variedSb 2 O 3 nanostructures is believed to be useful for the application of catalysis and flame retardance.